Dynamic Testing of Wholesale Power Market Designs: An Open-Source Agent-Based Framework - Sun, Junjie; Tesfatsion, Leigh (Computational economics, 2007)
In April 2003 the U.S. Federal Energy Regulatory Commission proposed a complicated market design--the Wholesale Power Market Platform ( WPMP )--for common adoption by all US wholesale power markets. Versions of the WPMP have been implemented in New England, New York, the mid-Atlantic states, the Midwest, the Southwest, and California. Strong opposition to the WPMP persists among some industry stakeholders, however, due largely to a perceived lack of adequate performance testing. This study reports on the model development and open-source implementation (in Java) of a computational wholesale power market organized in accordance with core WPMP features and operating over a realistically rendered transmission grid. The traders within this market model are strategic profit-seeking agents whose learning behaviors are based on data from human-subject experiments. Our key experimental focus is the complex interplay among structural conditions, market protocols, and learning behaviors in relation to short-term and longer-term market performance. Findings for a dynamic 5-node transmission grid test case are presented for concrete illustration. [PUBLICATION ABSTRACT]